2013
DOI: 10.1080/03630242.2013.767300
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equity and Health: Evaluating the Impact of Millennium Development Goal Three on Women's Health in South Asia

Abstract: Some progress has been made toward gender equity in South Asia, although the results have been mixed and inequities persist, especially in employment and government. While gender equity does not appear to have been related to female health outcomes, both must be addressed simultaneously as priority development targets and remain prerequisites to achieving the overall Millennium Development Goals. [Supplementary material is available for this article. Go to the publisher's online edition of Women & Health for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Findings from the literature review on the linkage between health outcomes and gender equity Our review of dimensions of gender equity identified five relevant articles [15,33,34,37,38] on gender equity indices. The gender development index (GDI) of the United Nations Development Program (UNDP) includes: life expectancy, literacy rate, school enrollment, and economic activity [15,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from the literature review on the linkage between health outcomes and gender equity Our review of dimensions of gender equity identified five relevant articles [15,33,34,37,38] on gender equity indices. The gender development index (GDI) of the United Nations Development Program (UNDP) includes: life expectancy, literacy rate, school enrollment, and economic activity [15,37].…”
Section: Resultsmentioning
confidence: 99%
“…The Gender Gap Index (GGI) includes: economic development, education, health, survival, and political participation [37]. The Gender Parity Index (GPI) includes: education, economic activity, and parliamentary representation [33]. The UN GII includes: reproductive health (i.e., maternal mortality and adolescent fertility), empowerment (i.e., parliamentary representation and secondary education attainment) and labor force participation [37,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrastructure development would contribute to the improved access to healthcare facilities and schools, increased investment, eliminated inequities, and decrease gender inequities (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Shannon et al measured the relationship between women’s health and average education, waged employment, and government participation in order to evaluate progress toward Millennium Development Goal Three in Southeast Asia. 5 Such indicators only provide snapshots into the realities of females’ lives. In order to capture the socio-cultural processes and structures that shape women’s lives, a more contextual understanding should be sought.…”
Section: Introductionmentioning
confidence: 99%